Bookplate in the context of Ukrainian printmaking at the turn of the XX and XXI centuries: Typological aspect - Romanenkova, Julia; Bratus, Ivan; Araya Berrios, Nina (Journal of Graphic Engineering and Design, 2023)
The article is dedicated to the examination of the bookplate of modern Ukraine, which starting from the 1990s entered the state of its revival and flourishing. A version of the bookplate typology, formed on the basis of pictorial motifs as the main classification criteria is proposed, while typologically bookplate is usually divided into groups based on the scope of use or the technique for creating graphic sheets. The reasons for the actualization of bookplate as a type of engraving at the turn of the 20th and 21st centuries, the factors that influenced its popularization outside the country, and the transformation of the functions of bookplate are considered. The role of collecting as one of the most powerful stimuli for the popularization of bookplate in the modern world of graphic arts is emphasized; the leading centers for the development of the bookplate in Ukraine at the beginning of the 21st century and the technique preferred by artists are indicated. Article history: Received (March 16, 2022); Revised (August 30, 2022); Accepted (November 6, 2022); Published online (June 1, 2023)